Repetition priming for face speech images: speech-reading primes face identification. - Campbell, R.; Haan, E. H. F. de (British Journal of Psychology, 1998)
Does speech-reading (classifying a facial image in terms of speech-sound) proceed independently of other face-reading skills? Repetition priming of face images was used to address this question. Earlier studies established that identity based decisions are sensitive to earlier exposure of images of a well-known person, but that face reading tasks such as expression or age classification may not be. We extended the repetition priming paradigm to speech-reading and in three experiments established that (a) identity decisions for personally familiar faces were sensitive to a previous image of that person's face making a speech-sound (identity decisions were primed by speech-reading), (b) speech-sound matching was not faster for known faces seen earlier in a different task (speech-reading was not primed by identification). We also found some evidence that knowledge of familiar faces could interfere with classification of face images for speech (unfamiliar faces were speech-read faster) and that repeating a speech-classification task could give rise to form rather than face-based priming. These findings are discussed in relation to the separability of speech-reading from other face processing tasks. Reprinted by permission of the publisher.